Problematika Perpanjangan Masa Jabatan Kepala Desa Menurut Prinsip Negara Demokrasi (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2023)
The demand for an extension of the village head's term of office becomes a dilemma, according to regulations the authority for extending the term of office of the village head is an open legal policy that forms political laws, but on the other hand, in democratic principles, we want restrictions on power. The research method used in this study is normative legal research using statutory and conceptual approaches. The results of the study show that the terms of office for village heads are not explicitly regulated in the 1945 Constitution of the Republic of Indonesia, such as the terms of office for the president and vice president and the term of office for regional heads. One of the reasons for the difference in arrangement is inseparable from the peculiarities of village governance in the Indonesian constitutional structure. According to the democratic principle that requires a limitation of power, an extension of the term of office for the village head will have the potential for abuse of power, such as corruption cases at the village level which occupy the top rank as the sector with the most corruption cases being prosecuted by law enforcement officials. Keyword: democracy; length of service; village head Abstrak Tuntutan perpanjangan masa jabatan kepala desa menjadi problematik, secara aturan kewenangan perpanjangan masa jabatan kepala desa merupakan kebijakan hukum terbuka (open legal policy) pembentuk undang-undang yang bersifat politis, namun di sisi lain dalam prinsip demokrasi menginginkan adanya pembatasan kekuasaan. Metode penelitian yang digunakan pada penelitian ini adalah penelitian hukum normatif dengan menggunakan pendekatan perundang-undangan dan konseptual. Hasil penelitian menunjukkan aturan mengenai masa jabatan kepala desa tidak diatur secara eksplisit dalam UUD NRI 1945 seperti halnya masa jabatan presiden dan wakil presiden serta masa jabatan kepala daerah. Salah satu alasan pembedaan pengaturan itu tidak terlepas dari kekhasan pemerintahan desa dalam struktur ketatanegaraan Indonesia. Menurut prinsip demokrasi yang menginginkan adanya pembatasan kekuasaan, perpanjangan masa jabatan kepala desa akan berpotensi terhadap penyalahgunaan kekuasaan (abuse ofpower) seperti kasus korupsi di tingkat desa yang menempati urutan teratas sebagai sektor kasus korupsinya paling banyak ditindak oleh aparat penegak hukum. Kata kunci: demokrasi; kepala desa; masa jabatan